Effects of Chemical Fertilizer and Bio-Extracts on the Growth and Yield of Butterhead Lettuce in Substrate Culture System - Luangsuwalai, Kanjana; Boonpatompol, Sahassawat; Kapkaeo, Chutima (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
Butterhead is a type of lettuce that is commonly consumed fresh. Currently, it is popular to grow fresh vegetables using a hydroponic solution system. The objective of this study was to examine the effect of using animal manure extract solutions on the growth of butterhead lettuce, grown in plastic pots using a soil substitute of sand mixed with rice husk charcoal. A randomized trial was conducted, consisting of six treatments: (1) chemical fertilizer (16-16-16), (2) vermicompost extract, (3) swine manure extract, (4) chemical fertilizer alternating with vermicompost extract, (5) chemical fertilizer alternating with swine manure extract, and (6) vermicompost extract alternating with swine manure extract. The results indicated that there are highly significant differences (P<0.01) in the growth (growth in terms of bush width, height, number of leaves, leaf length, and leaf width) and chlorophyll content within treatments. The results of the experiment can be divided into three groups: (1) butterhead lettuce supplied with chemical fertilizer, (2) butterhead lettuce grown with a chemical fertilizer solution alternating with animal manure extract, and (3) butterhead lettuce provided with animal manure extract. A significant difference (P<0.01) was found between the yield of each fertilizer, with the first group producing the most fresh weight of yield when compared to the other groups. The next highest producing yields were from chemical fertilizers alternating with swine manure extract solution, and chemical fertilizers alternating with vermicompost extract solution, respectively